(untitled) (Swiss Medical Weekly, 2017)
AIMS OF THE STUDY: In recent years, the Swiss Federal Office of Public Health (FOPH) granted exceptional licenses for the medical use of cannabinoids, typically for 6 months with possible extensions. A systematic review of cannabinoids for medical use commissioned by the FOPH supports the use of cannabinoids for the treatment of chronic pain and spasticity. However, little is known about the patients treated with cannabinoids. We aimed to study medical uses of cannabinoids as part of the FOPH’s programme of exceptional licenses. METHODS We examined all requests for medical use of cannabinoids sent to FOPH in 2013 and 2014. A standardised data sheet was developed to extract data from the files of approved requests. We extracted the duration of the licence, the year it was granted, and the payer of the therapy. At the level of the patient we collected the date of birth, sex, region of residence, diagnosis and the indication. Ethical approval was granted by the Ethics Committee of the Canton of Bern. RESULTS We analysed 1193 patients licenced for cannabinoid treatment in 2013 or 2014. During 2013, 542 patients were treated under the exceptional licencing programme (332 requesting physicians) compared with 825 in 2014 (446 physicians). Over half of patients (685; 57%) were women. The mean age was 57 years (standard deviation 15.0), chronic pain (49%) and spasticity (40%) were the most common symptoms, and co-medication was reported for 39% of patients. Seventy-eight different diagnoses were recorded, including multiple sclerosis (257 patients, 22%), soft tissue disorders (119, 10%), dorsalgia (97, 8.1%), spinal muscular atrophy (65, 5.5%) and paraplegia/tetraplegia (62, 5.2%). Licence extensions were granted to 143 patients (26.4%) in 2013 and 324 patients (39.3%) in 2014. There were substantial regional variations of the rates of patients treated with cannabinoids. On average, eight patients per 100 000 residents received an exceptional licence. Most patients (1083, 91%) paid out of pocket. CONCLUSIONS Exceptional licences for medical use of cannabinoids have increased substantially in Switzerland, with the programme including patients with a wide range of conditions.